If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -12 = 2x + 6 Reorder the terms: -12 + 5x = 2x + 6 Reorder the terms: -12 + 5x = 6 + 2x Solving -12 + 5x = 6 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -12 + 5x + -2x = 6 + 2x + -2x Combine like terms: 5x + -2x = 3x -12 + 3x = 6 + 2x + -2x Combine like terms: 2x + -2x = 0 -12 + 3x = 6 + 0 -12 + 3x = 6 Add '12' to each side of the equation. -12 + 12 + 3x = 6 + 12 Combine like terms: -12 + 12 = 0 0 + 3x = 6 + 12 3x = 6 + 12 Combine like terms: 6 + 12 = 18 3x = 18 Divide each side by '3'. x = 6 Simplifying x = 6
| 51-2x=7x+16 | | x^4-50x^2=49 | | 2(4+5)= | | -9=2x-3 | | x^3+3x^2=0 | | 2x-3=3-4 | | 6+2x=2+x | | 230-3x=33x+22 | | m^2+25=0 | | 2x+5x=8x | | 5-2(1+3x)=27 | | 2/+2= | | 2[8-3(4-y)]=3y-5 | | 2x+36=11x-54 | | 2/*2= | | 2c(c-d)= | | w=5n+5 | | 3+onehalf(5x+2)=14 | | 12-7x=123-28x | | 10x-18=102 | | 3a^2-7a-40=0 | | 0.75x+.05(20-x)=.10(66) | | -1=9+x | | x=3+4 | | (3x^3-5x^2+5x)+(5x^3+9x^2-12x)= | | 4-0.6x=-9 | | -3(3y+5)-17=-6(y+6)+3y | | 3r*3= | | 8x^2-6x=1 | | 2x+2y=56 | | 6p^2-11p-45=0 | | 14-10x=107-31x |